P15.04 Genital tract cellular activation and inflammation associated with highly prevalent sexually transmitted infections and bacterial vaginosis in adolescent women at risk for hiv infection. (13th September 2015) - Dabee, S; Barnabas, SL; Jaspan, HB; Jaumdally, SZ; Gamieldien, H; Masson, L; Lewis, D; Wallace, M; Bennie, T; Gray, C; Williamson, AL; Hope, T; et al.
Abstract : Introduction: The biological mechanisms underlying HIV risk in younger women is unclear. HIV is primarily transmitted across the genital mucosa and preferentially infects CD4 + T-cells. We investigated the influence of asymptomatic sexually transmitted infections (STIs) and bacterial vaginosis (BV) on CD4 + T-cell activation and inflammation in the genital tracts of adolescents from South Africa. Methods: Cervical cytobrush mononuclear cells were isolated from 148 adolescents (16–22 years) from Cape Town, and expression of T-cell activation and proliferation markers (CD38, HLA-DR, Ki67, CCR5) was measured by FACs. Adolescents were screened for BV (Nugent) and STIs ( C. trachomatis, N. gonnorhoea, T. vaginalis, M. genitalium, HSV-2) by PCR. For comparison, 11 HIV-negative adult women were included. Concentrations of 48 cytokines, chemokines and growth factors were measured in matching menstrual cups by Luminex. Results: Adolescents (median 18 years; IQR 17–20) had significantly higher frequencies of activated CD4 + T-cells (CD38 +, HLADR +, CD38 + HLADR + : each p < 0.0001) from cervical cytobrushes than adults although CCR5 expression was higher in adults. STIs and BV prevalence was very high, with 71% of adolescents having ≥1 STI and/or BV, and 42% being C. trachomatis positive. Adolescents with an STI, despite these being asymptomatic, had higher frequencies of activated and proliferating T-cells compared to those with no STI/BV (CD4 + CD38 + HLADR + : p = 0.047; CD4 + Ki67 + : p = 0.020). Women positive for chlamydia had significantly higher frequencies of CD4 + CD38 + T-cells (p = 0.006). Women with both STIs and BV had the most pronounced increase in CD4 + T-cell activation (CD38 + : p = 0.002; CD38 + HLADR + : p = 0.001; Ki67+: p = 0.002). Higher cervical T-cell activation marker expression was directly associated with increased genital cytokine profiles. Conclusion: Heightened levels of genital immune activation and inflammation found in South African adolescent females, partly due to the presence of asymptomatic STIs and BV could increase their risk for HIV infection.